The Semantic Network of Flood Hydrological Data for Kelantan, Malaysia. Issue 1 (March 2016) - Yusoff, Aziyati; Md Din, Norashidah; Yussof, Salman; Khan, Samee Ullah
Abstract: Every year, authorities in Malaysia are putting efforts on disaster management mechanisms including the flood incidence that might hit the east coast of Peninsular Malaysia. This includes the state of Kelantan of which it was reported that flood is just a normal event occurred annually. However, the aftermath was always unmanageable and had left the state to struggle for its own recoveries. Though it was expected that flood occurred every year, among the worst were in 1967, 1974, 1982 and recently in December 2014. This study is proposing a semantic network as an approach to the method of utilising big data analytics in analysing the huge data from the state's flood reading stations. It is expected that by using current computing edge can also facilitate mitigating this particular disaster.